Neurobehavioral features in medication-overuse headache - Franz Riederer; Roberto Pirrotta; Chantal Martin Soelch; Andreas R. Gantenbein; Adrian Scutelnic; Antonia Klein; Christoph J. Schankin; Peter S. Sándor (eNeurologicalSci)
Background: Medication-overuse headache (MOH) has been related to the spectrum of dependence behavior and impaired orbitofrontal cortex function. Alexithymia is a trait comprising deficits in identifying self-emotions and perception. It was the aim of the study to investigate impulsivity and alexithymia, in patients with MOH and perform correlations with cerebral grey matter. Material and methods: Patients with chronic migraine and MOH according to ICHD criteria from a tertiary headache clinic and healthy controls were investigated by a single psychiatrist, using clinical scales for self-control (BIS-11) and alexithymia (TAS-20) and screened for dependence based on DSM-IV criteria. Correlations of BIS-11 and TAS-20 with cerebral grey matter were analysed with the SPM based toolbox CAT12, using high resolution T1weighted MRI-Sequences acquired on a 3 T scanner. Results: MRI data were available from 30 MOH patients (24 women) and 47 healthy controls (26 women). MOH patients had increased impulsivity (62.2 ± 11.1 vs. 55.7 ± 7.2; p = 0.007) and alexithymia (49.8 ± 14.8 vs. 38.0 ± 6.5; p < 0.001). Analyzing only women, the results remained significant. Ninety percent of patients fulfilled DSM-IV criteria for substance dependence. There was a positive correlation between impulsivity and grey matter in the left middle orbital gyrus in healthy controls but not in patients (p < 0.05, corrected). No correlations with alexithymia and cerebral grey matter were found. Conclusions: The present study suggests a neurobehavioral basis for MOH, consisting of impaired impulse control, and self-perception along with features of substance dependence. Although decreased orbitofrontal cortex volume was confirmed in this MOH cohort, impulsivity and alexithymia were not correlated with this structural abnormality.